2011
DOI: 10.1186/1756-3305-4-116
|View full text |Cite
|
Sign up to set email alerts
|

Questionnaire-based approach to assess schoolchildren's physical fitness and its potential role in exploring the putative impact of helminth and Plasmodium spp. infections in Côte d'Ivoire

Abstract: BackgroundDisability weights (DWs) are important for estimating burden of disease in terms of disability-adjusted life years. The previous practice of eliciting DWs by expert opinion has been challenged. More recent approaches employed quality of life (QoL) questionnaires to establish patient-based DWs, but results are ambiguous.MethodsIn early 2010, we administered a questionnaire pertaining to physical fitness to 200 schoolchildren in Côte d'Ivoire. Helminth and Plasmodium spp. infections were determined and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…Our results are in contrast to recent studies of other NTDs that suggest no clear differences in HrQoL between infected and non-infected health states [14], [16]. Increasing severity of intestinal schistosomiasis, whether caused by S. japonicum in P.R.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Our results are in contrast to recent studies of other NTDs that suggest no clear differences in HrQoL between infected and non-infected health states [14], [16]. Increasing severity of intestinal schistosomiasis, whether caused by S. japonicum in P.R.…”
Section: Discussioncontrasting
confidence: 99%
“…Measuring HrQoL is an important outcomes indicator in evaluating health-care interventions and treatments, in understanding the burden of disease, in identifying health inequalities, in allocating health resources, and in epidemiological studies and health surveys [19]. Unlike in other chronic conditions such cancer and sickle cell disease where HrQoL tools have been widely used, for NTDs these tools have only been used to assess the burden of advanced schistosomiasis (using EQ-5D plus or WHO QoL-bref questionnaires) [13], [15], [20], soil-transmitted helminthes (using both EQ-5D and SF-12) [16], and echinococcosis (using SF-12) [21], and to assess the burden of polyparasitism in Cote d'Ivoire (using SF-36v2 questionnaire but only the physical scale) [14]. SF-12 has also been used to describe the impact of acute schistosomiasis on quality of life in a group of travelers returning from a luxury safari trip in Tanzania [22].…”
Section: Introductionmentioning
confidence: 99%
“…haematobium , S . mansoni , hookworm, Ascaris lumbricoides and Plasmodium spp) [17], but this questionnaire focused on physical functioning and did not include an emotional dimension. Another Chinese study investigated the quality of life in patients with advanced schistosomiasis, but this only included patients above 30 years of age and is not comparable to the present study [16].…”
Section: Discussionmentioning
confidence: 99%
“…japonicum infections, and in Côte d’Ivoire another questionnaire (SF-36v2) was used to assess the physical burden of polyparasitism [17]. Currently, only two studies have quantified the effect of schistosome infection on overall wellbeing or quality of life using the Pediatric Quality of Life Inventory (PedsQL) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…The climate in the area is tropical with two rainy seasons lasting from April to July and from mid-September to November. The study site was selected based on previous work conducted in Grand Moutcho that had shown a high endemicity of S. haematobium [30,31] . All children attending grades 3, 4, 5 and 6 in the primary school Grand Moutcho I were invited to participate.…”
Section: Methodsmentioning
confidence: 99%